Catalytic Asymmetric Conjugate Addition of Tritylthiol to Azadienes with a Bifunctional Organocatalyst. Issue 8 (12th June 2018) - Gu, Zheng; Xie, Jiao‐Jiao; Jiang, Guo‐Fang; Zhou, Yong‐Gui
Abstract: A highly enantioselective sulfa‐Michael addition of tritylthiol to azadienes catalyzed by a bifunctional squaramide organocatalyst is described, giving the chiral aminothioethers bearing benzofuran motif with high yields and up to 94 % of enantioselectivity. Notably, the aromatization to form the benzofuran is the driving force. Abstract : Synthesis of aminothioether derivatives : A facile protocol for synthesis of the aminothioether derivatives through the bifunctional squaramide organocatalyst‐catalyzed asymmetric conjugate addition of thiols to azadienes is developed with excellent yields and up to 94 % of enantioselectivity.